Implikasi Disiplin dan Stres Kerja Terhadap Kinerja Karyawan di Rumah Sakit Ibu Anak - Felida, Elisabeth Mega; Yuniastuti, Rina Milyati; Vitratin, Vitratin; K Harahap, Aderina; Hairani, Tuti (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2023)
Low levels of employee work discipline and high levels of work stress causes the decreased of employee performance. This problem become an internal problem at the Santa Anna Maternal and Child Hospital in Teluk Betung. The aim of this research is to determine the implications of work discipline and work stress towards employee performance at maternal and child hospitals. The researcher used quantitative research method with the population of 169 employees. The research data was obtained from interview and survey. The instrument wastested using validity and reliability tests, while data analysis used the t test and F test. The result of the t test shows that the work discipline variable has an effect towards employee performance, the work stress variable has no effect towards employee performance at the Santa Anna Marital and Child Hospital in Teluk Betung. The result of the F test shows that work discipline and work stress affects the employee performance. The implications of thisresearch is to give attention on work discipline and work stress in order to improve the employee performance. For further research, it is recommended to add moderating variables or intervening variables.